Les gouvernants congolais : récit d’une trajectoire controversée - LIFOLI BALEA, Jean-Pierre (IJRDO - Journal of Social Science and Humanities Research, 2018)
After the elections organized in 2006 in Democratic Republic of Congo, this country knew the governing presenting a controversial profile. It was a group of governing descended of the modest families and having a weak level of instruction. They were to more of 70% of former teachers of the primary schools and secondary, of the male nurses, of the civil servants of the state and some former tradesmen. Arrived to the power, numerous among them passed all their time to the studies in the university. Of others that could work to find some solutions to the difficulties met by the people of that they got the political mandate, chose to use instead of serving the people. It is why the RDC knew a category of the governing incompetent, corrupting and corrupt, little anxious of the people’s happiness.